2008
DOI: 10.1021/jf802253s
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Heating of Tea Residue Yields Polysaccharides, Polyphenols, and Plant Biopolyester

Abstract: Microwave heating was used to produce aqueous-soluble components from green, oolong, and black tea residues. Heating at 200-230 degrees C for 2 min extracted 40-50% of polysaccharides and 60-70% of the polyphenols. Solubilization of arabinose and galactose by autohydrolysis occurred with heating above 170 degrees C, whereas heating above 200 degrees C was necessary to solubilize xylose. Catechins were soluble in water by heating at low temperature (110 degrees C); however, new polyphenols having strong antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 24 publications
1
51
0
2
Order By: Relevance
“…Like green tea, green tea waste also contains phenolic compounds (Cai et al, 2001;Tsubaki et al, 2008Tsubaki et al, , 2010An et al, 2011;Toh et al, 2010), while the content of phenolic compound would be much In the present study muscle crude protein and crude lipid were not different among groups, which were consistent with previous findings where no changes in body composition, whole-body lipid concentration or muscle lipid concentration were observed in rainbow trout fed on EGCG (epigallocatechin-3-gallate, Thawonsuwan et al, 2010) or in juvenile olive flounder fed on various sources of green tea (Cho et al, 2007).…”
Section: Effect Of Gtw On Growth and Feed Efficiency Ratio Of Grass Carpmentioning
confidence: 99%
See 2 more Smart Citations
“…Like green tea, green tea waste also contains phenolic compounds (Cai et al, 2001;Tsubaki et al, 2008Tsubaki et al, , 2010An et al, 2011;Toh et al, 2010), while the content of phenolic compound would be much In the present study muscle crude protein and crude lipid were not different among groups, which were consistent with previous findings where no changes in body composition, whole-body lipid concentration or muscle lipid concentration were observed in rainbow trout fed on EGCG (epigallocatechin-3-gallate, Thawonsuwan et al, 2010) or in juvenile olive flounder fed on various sources of green tea (Cho et al, 2007).…”
Section: Effect Of Gtw On Growth and Feed Efficiency Ratio Of Grass Carpmentioning
confidence: 99%
“…Tea waste or tea residue also contains polyphenols, which was reported to have strong antioxidant activity (Tsubaki et al, 2008). The present result shows that serum T-AOC in GTW group are higher than that in BD group, indicating that fish fed GTW had higher antioxidant capacity, which is consistent with previous result of Nishida et al, (2006), who found higher plasma anti-oxidative activity in cattle fed with green tea waste silage.…”
Section: Effect Of Gtw On Serum Biochemical Parameters Of Grass Carpmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwaves enable rapid and uniform heating of polar substances by direct and internal heating generated by friction of dipole rotations. Microwave heating has been widely applied in organic chemistry (Perreux and Loupy, 2001;Lidström et al, 2001), extraction methods (microwave-assisted extraction; MAE) (Rostagno et al, 2007, Ookushi et al 2006, Tsubaki et al 2008, and pretreatment for lignocellulosic materials prior to enzymatic hydrolysis (Azuma et al, 1984;Magara et al, 1988). Microwave heating is regarded as a kind of subcritical water treatment and presents an alternative method of autohydrolysis that partially overcomes the defects of previous autohydrolysis processes (Azuma et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Due to a direct heating mechanism, the fermentation reaction is terminated in a shorter time and some volatiles are retained. Studies have been conducted to determine the effects of microwave applications on the quality constituents of various tea samples (Tsubaki et al 2008;Dong et al 2011). Huang et al (2007) studied the inactivation of enzymes in tea leaves using oven and microwave heating methods and found that microwave treatment was more effective in preserving the quality of processed green tea in terms of polyphenol content and colour properties.…”
mentioning
confidence: 99%